1996
DOI: 10.1021/jp961134v
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Thermochemistry of C5H5+ Isomers:  Which C5H5+ Isomer Is the Most Stable?

Abstract: G2, G2(MP2), and G2(B3LYP/MP2/CC) calculations show the vinylcyclopropenyl cation 3 to be the lowest energy of the C 5 H 5 + isomers. The calculated energy difference between the cyclopentadienyl cation 2 and the vinylcyclopropenyl cation 3 is very small (11.9 and 13.1 kJ mol -1 at G2 and G2(B3LYP/MP2/CC) levels, respectively), and higher level corrections used in G2, G2(MP2), and G2(B3LYP/MP2/CC) theories have a crucial effect upon it. Calculations using G2 theory without higher level corrections indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…For 2 we previously calculated a value of À14.3 kcal mol À1 at the CASPT2A C H T U N G T R E N N U N G (14,15)/[4s3p2d/3s1p]// OLYP/TZ2P level, [8] and values in the range from À2.9 to À10.6 kcal mol À1 have been found with G2, CCSD(T), MPn, and B3LYP calculations. [2,39,[41][42][43]53] The OLYP/6-311GA C H T U N G T R E N N U N G (d,p) DE ST value for 2 is thus well within the expected interval.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…For 2 we previously calculated a value of À14.3 kcal mol À1 at the CASPT2A C H T U N G T R E N N U N G (14,15)/[4s3p2d/3s1p]// OLYP/TZ2P level, [8] and values in the range from À2.9 to À10.6 kcal mol À1 have been found with G2, CCSD(T), MPn, and B3LYP calculations. [2,39,[41][42][43]53] The OLYP/6-311GA C H T U N G T R E N N U N G (d,p) DE ST value for 2 is thus well within the expected interval.…”
mentioning
confidence: 53%
“…This feature was first discussed by Borden and Davidson, [40] and later by others. [39,[41][42][43][44][45] Recently, a photoelectron spectroscopic study has confirmed the quasidegeneracy of the two singletstate structures. [46] At the OLYP/ 6-311GA C H T U N G T R E N N U N G (d,p) level the first (2 s) has C 2v symmetry, while the second (2 s') has C 2 symmetry with a C 2v -symmetric transition state located 0.6 kcal mol À1 above.…”
Section: Singlet-state Geometriesmentioning
confidence: 94%
“…This fragment ion has an apparent D f H = 12.67 ± 0.10 eV. Five isomers of C 5 H þ 5 are known either experimentally or on the basis of calculations [35,77]. In our case the m/z = 65 ion is most probably HC"CCHCH@CH þ 2 (Pent-1-en-4-yn-3-yl radical ion) which has a reported D f H = 11.73 eV [29].…”
Section: Benzimidazole C 7 H 6 Nmentioning
confidence: 99%
“…Selected bond lengths [] and angles [8] for the second independent molecule in the unit cell (P(6) is the apical phosphorus atom): P(4)ÀC (16) + ion than a square-basedpyramidal structure. [18,19] These observations encouraged us to survey systematically the potential-energy surface (PES) of the model cation [C 2 H 2 P 3 ]…”
Section: Dedicated To Professor Manfred Regitzmentioning
confidence: 99%